The presidential papers of Ramon Magsaysay a plan for their organization, administration and development - Nivera, Pat I.; Vallejo, Rosa M.; Mercado, Filomena C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1971)
Records act as the tangible memory of nations, organizations and individuals. These are generally classified into textual, pictorial and cartographic records. The records created by and for the President of the Philippines, better known as his Papers, reflect much of his own actuations, the state of the country at a given period and the nation's international position. As such, they are valuable sources for the writing of political, socio-economic or diplomatic history, for biographies; for the documentation of events or for tracing the course of public administration and government machinery.
In the United States, the collection and conservation of such Papers are embodied in a definite program of preservation through the Presidential Papers Program of the Library of Congress.To date, ten men have occupied the position of President of the Philippines, but the Papers of only three (Aguinaldo, Quezon and Laurel), have so far received some measure of care and preservation.
This thesis lays out a plan for the preservation of the Papers of the late President Magsaysay and their subsequent opening to research. It expresses a hope that the plan will serve as a model for the preservation of other Presidential Papers and recommends legislation for this process because the Presidential Papers form a part of our national heritage.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Magsaysay, Ramon, Prs. Philippines -- 1907-1957.; President -- Philippines